University Evolution, Entrepreneurial Activity and Regional Competitiveness - Audretsch, David; Lehmann, Erik; Meoli, Michele; Vismara, Silvio (International Studies in Entrepreneurship, 2016)
This book aims to bring together different contributions highlighting how the recent changes that modify universities' activities, such as the necessity to internationalize and crucially rely on third party funding, and the new entrepreneurial trajectories stemming from the recent economic-financial crisis, contribute to emphasize the existing differences between successful and lagging regions, as occurred at a country level (e.g. Southern Europe). This book should be of interest to economists, sociologists, political scientists as well as to policy makers and practitioners involved in the creation of value at a local level.